Acute infusion of angiotensin II regulates organic cation transporters function in the kidney: its impact on the renal dopaminergic system and sodium excretion - Fernandez, Belisario Enrique (2020)
Fil: Fernandez, Belisario Enrique. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.